Influence of antipsychotic medications on hyperlipidemia risk in patients with schizophrenia: evidence from a population-based cohort study and in vitro hepatic lipid homeostasis gene expression - Wu, Tien-Yuan; Tien, Ni; Lin, Cheng-Li; Cheah, Yu-Cun; Hsu, Chung Y.; Tsai, Fuu-Jen; Fang, Yi-Jen; Lim, Yun-Ping (Frontiers in Medicine, 2023)
Schizophrenia increases the risk of mortality and cardiovascular disease (CVD) risk. However, the correlation between antipsychotics (APs) and CVD remains controversial. Hyperlipidemia is a significant risk factor for CVD. We conducted a nationwide population-based retrospective cohort study to investigate the effects of APs on the risk of hyperlipidemia and lipid homeostasis gene expression. We used data from the Longitudinal Health Insurance Database of Taiwan on new-onset schizophrenia patients and a comparison cohort without schizophrenia. We used a Cox proportional hazards regression model to analyze the differences in hyperlipidemia development between the two cohorts. Furthermore, we examined the effects of APs on the hepatic expression of lipid homeostasis-related genes. After adjusting for potential interrelated confounding factors, the case group (N = 4,533) was found to have a higher hyperlipidemia risk than the control cohort (N = 4,533) [adjusted hazard ratio (aHR), 1.30, P < 0.001]. Patients with schizophrenia without APs had a significantly higher risk of hyperlipidemia (aHR, 2.16; P < 0.001). However, patients receiving APs had a significantly lower risk of hyperlipidemia than patients not receiving APs (all aHR  0.42, P < 0.001). First-generation antipsychotics (FGAs) induce the expression of hepatic lipid catabolism genes in an in vitro model. Patients with schizophrenia had a higher risk of hyperlipidemia than controls; however, compared with non-treated patients, AP users had a lower risk of hyperlipidemia. Early diagnosis and management of hyperlipidemia may help prevent CVD.